Pengaruh Foot Massage terhadap Penurunan Tekanan Darah dan Stres Psikologis pada Keluarga Pasien Gagal Ginjal Kronik - Fajaruddin Nasution; Iqbal Maidira Darmansyah; Dwi Sinta Larasati; Elis Anggeria (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Chronic disease (CKD) a clinical condition because of conclusive changes in kidney capacity and construction. Psychological status is a direct risk factor for hypertension. This study aims to determine the effect of foot massage on reducing in blood pressure and psychological stress in families of chronic kidney failure at Rasyida Special Renal Hospital Medan. The study design was a quantitative method with a quasi-experimental design through a one-group pre-test post-test. The population in this study was 35 patients' families. The sampling technique was Saturated Sampling and a sample of 35 people. Methods using questionnaires Perceived Stress Scale (PSS) and observation sheets. The bivariate analysis using of the Wilcoxon test. The results of the study before giving foot massage therapy to the patient's family failed to win the attention of 19 people (54.3%) and experiencing stress as many as 25 people (71.4%), and after giving therapy of foot massage a large number of people's blood (74.3%) ) there was a decrease in stress levels to mild as many as 26 people (74.3%), obtained p-value 0.000, it can say that there is an effect of foot massage on reducing blood pressure and psychological stress in chronic kidney failure families.